Peak torque and knee kinematics during gait after eccentric isokinetic training of quadriceps in healthy subjects - Poletto,PR (2008)
OBJECTIVE: To evaluate the effects of eccentric isokinetic training on knee range of motion (ROM) of healthy subjects. METHODS: The knee extensor and flexor isokinetic peak torques and ROM of flexion/extension and varus/valgus knee movements during gait of 18 healthy men (21.7±2.2 years; 1.73±0.10m; 68.7±9.4kg; body mass index: 22.6±2kg/m²) were analyzed, before and after six weeks of bilateral eccentric isokinetic training of the knee extensors at 30º/s. RESULTS: The knee extensor torque increased in both limbs (right, from 229±54 to 304±53Nm; p<0.01; and left, from 228±59 to 311±63Nm; p<0.01), without any difference in torque gain between them. The knee flexor peak torque increased (from 114±30 to 123±22Nm; p<0.05), but the hamstrings/quadriceps (H/Q) ratio decreased (from 0.5±0.08 to 0.39±0.07; p<0.01) after the training. There were no differences in the flexion/extension and varus/valgus movements after the training, except for a small change (4°) in valgus for the left knee. CONCLUSIONS: The eccentric isokinetic training of the knee extensors increased the extensor torque and decreased the H/Q ratio, although the effect on the gait pattern seemed negligible in healthy subjects. Associated training for flexors, complementary to the extensor training, seems to be necessary for balance between knee agonists and antagonists.